Metformin does not compromise energy status in human skeletal muscle at rest or during acute exercise: A randomised, crossover trial - Jonas M. Kristensen; Christian Lillelund; Rasmus Kjøbsted; Jesper B. Birk; Nicoline R. Andersen; Lars Nybo; Karin Mellberg; Anudharan Balendran; Erik A. Richter; Jørgen F. P. Wojtaszewski (Physiological Reports, 2019)
Abstract 5´AMP–activated protein kinase (AMPK) is a mediator of a healthy metabolic phenotype in skeletal muscle. Metformin may exacerbate the energy disturbances observed during exercise leading to enhanced AMPK activation, and these disturbances may provoke early muscular fatigue. We studied acute (1 day) and short‐term (4 days) effects of metformin treatment on AMPK and its downstream signaling network, in healthy human skeletal muscle and adipose tissue at rest and during exercise, by applying a randomized blinded crossover study design in 10 lean men. Muscle and fat biopsies were obtained before and after the treatment period at rest and after a single bout of exercise. Metformin treat ment elicited peak plasma and muscle metformin concentrations of 31 μM and 11 μM, respectively. Neither of the treatments affected AMPK activity in skeletal muscle and adipose at rest or during exercise. In contrast, whole‐body stress during exercise was elevated as indicated by increased plasma lactate and adrenaline concentrations as well as increased heart rate and rate of perceived exertion. Also whole‐body insulin sensitivity was enhanced by 4 days metformin treatment, that is reduced fasting plasma insulin and HOMA‐IR. In conclusion, acute and short‐term metformin treatment does not affect energy homeostasis and AMPK activation at rest or during exercise in skeletal muscle and adipose tissue of healthy subjects. However, metformin treatment is accompanied by slightly enhanced perceived exertion and whole‐body stress which may provoke a lesser desire for physical activity in the metformin‐treated patients.